Metabolic Regulation of Hypoxia-Inducible Factors in Hypothalamus - Du, Dan; Zhang, Yugang; Zhu, Canjun; Chen, Hong; Sun, Jia (Frontiers in Endocrinology, 2021)
The earliest function of hypoxia-inducible factor (HIF) was to respond to hypoxia or hypoxic conditions as a transcription factor. Recent studies have expanded our understanding of HIF, and a large amount of evidence indicates that HIF has an important effect on central regulation of metabolism. The central nervous system's response to glucose, inflammation, and the central influence of hormones on systemic metabolism are all regulated by HIF to varying degrees. In the hypothalamus, HIF mostly plays a role in inhibiting energy uptake and promoting energy expenditure, which is not only dependent on the single effect of HIF or on a single part of the hypothalamus. In this paper, we summarize the recent progress in central regulation of metabolism, describe in detail the role of HIF in various functions of the hypothalamus and related molecular mechanisms, and reveal that HIF is deeply involved in hypothalamic-mediated metabolic regulation.